(untitled) (World Bulletin of Physical Education and Sports Science, 2025)
Wearable technology, such as pedometers, smartwatches, and fitness trackers, offers a promising approach to monitor and enhance physical activity among adolescents. This study investigates the impact of wearable devices on student activity levels, health awareness, and engagement in physical education classes across Sweden, Germany, and the Netherlands. Data were collected from 360 students aged 12–16 in 12 schools per country. Results indicate that wearable devices significantly increase daily step counts, moderate-to-vigorous physical activity, and student motivation. Challenges include device compliance, data accuracy, and digital literacy. The study recommends integrating wearable technology into PE curricula, providing teacher guidance, and addressing ethical considerations regarding data privacy.